Teknik Olah Vokal Dengan Kemampuan Bernyanyi Pada Paduan Suara SMA Swasta PGRI 20 Siborongborong Tapanuli Utara - Diva Threcia Purba; Eben Haezarni Telaumbanua; Aprinaldi P Simarangkir (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The aim of this research is to find out good and correct vocal techniques for body posture, breathing, articulation, phrasering when singing in a choir. In this research, researchers used qualitative research methods using observation, interviews and documentation. This research was carried out by collecting information through field research to obtain results which were processed into accurate data. The research process carried out as data collection is: photos, videos and interviews. The results of this research show that the process of implementing vocal technique training in singing the song Sing Alleluia Clap Your Hands is training in body posture, breathing, articulation and phrasing. By singing the song Sing Alleluia Clap Your Hands sung acapella. In the score, this song is performed with full energy and an allegretto tempo (rather fast) with a 4/4 beat and combined with handclaps. From all the observations and methods that the author has used in conducting research, the vocal techniques of body posture, breathing, articulation and phrasing in singing the song Sing Alleluia Clap Your Hands are very important. To obtain good and correct vocal techniques, several steps must be taken to master good posture, breathing, articulation and phrasing techniques, namely: practicing breathing before singing, positioning the body in a good and correct posture, using diaphragmatic breathing. to produce a more powerful voice and understand where the breath is divided in the score, pay attention to the pronunciation of each word well, understand the meaning of the song by breaking up sentences correctly.